Analysis of Modification and Dynamic Characteristic of Timing Gear of Diesel - Jinlin Bai; Junsheng Zhao; Shubin Yang; Zhengwen Li; Chaodong Zhang (Jixie chuandong)
Aiming at the phenomenon of timing gear whine noise caused by high power density diesel engine, considering the transmission error and other factors, a 12V150 diesel engine is taken as the research object and valve train timing gear transmission system model is established by Romax software. The tooth surface loading and peak value and fluctuation range of transmission error under the excitation of the transmission error are analyzed. The size and distribution of the unit length load of the tooth surface is used as the standard, the middle gear pair of the timing gear system is modified. It shows that the tooth surface load can be distributed to the middle part by gear modification, the load distribution area increase and the load reduce, transmission error reduce, two different modification schemes are compared and analyzed, the vibration acceleration is reduced by 38% and 56.9% respectively.